Cationic Hofmeister Series of Wettability Alteration in Mica–Water–Alkane Systems - Bera, B. (Langmuir, 2018)
[Image: see text] The specific interaction of ions with macromolecules and solid–liquid interfaces is of crucial importance to many processes in biochemistry, colloid science, and engineering, as first pointed out by Hofmeister in the context of (de)stabilization of protein solutions. Here, we use contact angle goniometry to demonstrate that the macroscopic contact angle of aqueous chloride salt solutions on mica immersed in ambient alkane increases from near-zero to values exceeding 10°, depending on the type and concentration of cations and pH. Our observations result in a series of increasing ability of cations to induce partial wetting in the order Na(+), K(+) < Li(+) < Rb(+) < Cs(+) < Ca(2+) < Mg(2+) < Ba(2+). Complementary atomic force microscopy measurements show that the transition to partial wetting is accompanied by cation adsorption to the mica–electrolyte interface, which leads to charge reversal in the case of divalent cations. In addition to electrostatics, hydration forces seem to play an important role, in particular for the monovalent cations.